Taxi reservation system of Batu Pahat taxi association - Hamzah, Rosnamidar; Kasim, Shahreen; Hassan, Rohayanti; Mahdin, Hairulnizam; Ramli, Azizul Azhar; Md Fudzee, Mohd Farhan; Salamat, Mohamad Aizi (Zibeline Internasional Publishers, 2018)
Taxi reservation system is developed for the Association of Taxi Companies Batu Pahat. The system is developed based website aims to facilitate users taxi company to make a reservation. Application of this book will be approved by the administrator. The system administrator can update the taxi booking application and issue a report on consumer booking system. This system was designed and developed using the prototype model approach has four phases: Planning, Analysis, Design and Implementation. Interfaces are used to develop this system is Adobe Dreamweaver CS6. The programming language used is PHP (Hypertext Pre-processor) and XAMMP used as a web server. With the taxi booking system, consumers will be able to make reservations online as well as make it easier and save time. Factors colour selection, concept presentations, text and colours were chosen to suit the theme of the show and the ease of use and feel the comfort in using this system.